Protocol for Testing Flexural Strength, Flexural Modulus, and Fatigue Failure of Cementitiously Stabilized Materials Using Third-Point Flexural Beam Tests - Mandal, Tirupan; Tinjum, James M.; Gokce, Ahmet; Edil, Tuncer B. (AMER SOC TESTING MATERIALS, 2016)
In this study, a testing protocol was developed to measure the flexural strength, flexural modulus, and fatigue failure of cementitiously stabilized materials (CSMs) for both lightly and heavily stabilized soils. Four soils (sand, gravel, silt, and clay) and four binders (cement, lime, class C fly ash, and class F fly ash) were used in this study. Beam specimens (100mm high by 100mm wide by 400mm long) were prepared and tested using third-point flexural beam tests. A fatigue distress model was developed, and the data from this study was validated using other existing stress-based fatigue models. Results indicated that the testing protocol could be used to determine the flexural strength, flexural modulus, and fatigue behavior of the cementitiously stabilized layers (CSL). A stress-based fatigue performance model was a good fit for the whole range of CSMs, which is needed to predict the fatigue performance of CSL in the field and to determine the fatigue life of the CSLs.
Keywords: testing protocol; flexural strength; flexural modulus; fatigue; cement-stabilized materials; AGGREGATE; Engineering; Geology